Differential response of normal and transformed mammary epithelial cells to combined treatment of anti-miR-21 and radiation. (3rd April 2017) - Radulovic, Vanja; Heider, Theresa; Richter, Sabine; Moertl, Simone; Atkinson, Michael J.; Anastasov, Nataša
Abstract: Purpose: MicroRNA miR-21 has emerged as a therapeutic target in the treatment of breast cancer. This study was designed to compare the responses of breast cancer cells and non-transformed breast epithelial cells to a combined regimen of miR-21 inhibition and radiation. Materials and methods: The MDA-MB-361 (breast cancer) and MCF-10A (non-transformed mammary epithelial) cell lines were used for the comparison in this in vitro study. The stable knockdown of miR-21 was performed by using lentiviral approach. The response of the cells was monitored 4, 24 and 48 h after the irradiation with 0.25 and 2.5 Gy, using sham-irradiated cells as controls. The response of the cells was established by performing various functional assays – cell viability and cell attachment, clonogenic survival, cell cycle analysis and 3D microtissue formation. Results: The knockdown of miR-21 induced significant increase in apoptosis and growth delay in MDA-MB-361 cancer cells compared to non-transformed MCF-10A cells. After combined radiation and anti-miR-21 treatment, MDA-MB-361 cells show reduced cell growth and viability what is presented in their inability to form colonies. MCF-10A cells were not as sensitive to the combined treatment and that has also been confirmed with colony forming assay. Conclusions: Cellular response to a combined treatment of anti-miR-21 and radiation is different between cancer and non-cancer cells which highly support the idea of linking miR-21 inhibitor and radiation treatment in the future therapeutic approaches for breast cancer.